Development of tempe flour-enriched snacks to prevent anemia in adolescent girls - Hidayanti, Lilik; Rahfiludin, Mohammad Zen; Nugraheni, Sri Achadi; Murwani, Retno (Progress in Nutrition, 2023)
Anemia is still a nutritional problem among adolescent girls around the world. Snack consumption habits among adolescent girls are increasing, even though snacks contain much energy but are low in protein and iron. Tempe, a nutritious and inexpensive indigenous food of Indonesia, steadily gaining global recognition, is rich in protein and iron. This study aimed to develop tempe flour-enriched snacks to prevent anemia among adolescent girls. This research and development (R&D) study consists of four stages. Firstly, to determine a snack carrier through a survey of snack preferences among 356 female adolescent students of Junior High School in Tasikmalalaya City. Secondly, the product formulation uses three different percentages of tempe flour, i.e., 40% (S1), 30% (S2), and 20% (S3) in the 100g dough. Thirdly, sensory tests were carried out on 80 young women. Finally, the determination of the nutritional content (energy, protein, carbohydrate, fat, iron, and beta carotene) of the selected formula results from a sensory test. The preference test results showed that snack made of cassava flour, salted and not fried, was chosen as “carrier” based on the most preferred by participants (90.4%). The results showed no difference in all sensory tests (taste, smell, color, texture, and overall) between the three formulas. The S2 Formula was chosen because it had the highest average of all sensory scores compared to the others. Analysis nutritional content of the S2 formula per 100g showed an energy content of 239.89 kcal, protein 12.6 g, carbohydrate 27.1 g, fat 9.01 g, iron 1.46 mg, and beta carotene 251.46 µg. Adding tempe flour to cassava flour based-snack can increase protein and iron content. This makes it suitable as a food-based approach (FBA) to prevent anemia in adolescent girls. Clinical trials are needed to prove that Tempe flour-enriched snacks can prevent anemia in adolescent girls.